Erratum to: Sharp Bounds and Simple Approximations for the Erlang Delay and Loss Formulas - Harel, Arie (Management Science, 1988)
Erratum to Sharp Bounds and Simple Approximations for the Erlang Delay and Loss Formulas (Vol. 34, No. 8 (August 1988), pp. 959–972.)